Youth, High School in the Semi-Arid Northeast II - Oliveira, Rosa Maria (2025)
The text presented is part of research carried out at PPGIES in 2022 and discusses the problem of youth, the target audience of high school in the context of the Semi-arid Northeast II of Bahia. It reflects on the concept of youth in relation to the current scenario of high school, the importance of strengthening the rights of young people and actions intrinsic to them, as well as the need and urgency of the public power to develop and implement public policies for young people in a participatory way. addresses the relevance of youth protagonism.The study has an option for the qualitative methodology using semi-structured interviews conducted with high school students. presents as a question: What is the profile and perceptions of high school students from a public school in Jeremoabo located in the semi-arid northeast II, about youth? The objective is to know and analyze the profile and perceptions of high school students from a public school in Jeremoabo about youth.The results indicated that the profile of the students is composed of the diversity of young people from the city and the countryside, in different social, cultural and economic conditions that conceive the youth as capable of living the youth protagonism. The conclusion indicates that the group is configured as young people who differ from their living conditions and expectations, as well as indicates that they demand specific public policies for young people, which can enhance youth protagonism.